Correlation Between Determinant Factors and Early Initiation of Breastfeeding Practice in UPT Nglipar 1 Public Health Center - Ayu, Suci Musvita; Hergianingrum, Winda Juliani (Universitas Ahmad Dahlan, 2021)
Background: The coverage of Early Initiation of Breastfeeding (EIB) in Public Health Centers in Gunung Kidul Regency was 84.79%. Unit Pelaksana Teknis (UPT) Nglipar 1 Public Health Center has an EIB coverage of 75.86%. The amount is below the average of EIB coverage of all Public Health Centers in Gunung Kidul. This study aims to determine the factors that influence EIB at the UPT Nglipar 1 Public Health Centers. Method: The research employed observational analytic with a cross-sectional study design. The sample of this study was 45 mothers who were used as primary data. The sampling technique used to select participants was purposive sampling. Additionally, a questionnaire was also employed as research instrument. The population in this study were all mothers who gave birth in the UPT Nglipar 1 Public Health Center's working area. The study's independent variables were the mother's knowledge, husband's support, and health personnel support. The dependent variable is the Early Initiation of Breastfeeding. The data were analyzed using the chi-square method. Results: The results suggested that the relationship between maternal knowledge and EIB was indicated with p-value < 0.05. It showed that there was no relationship between partner support and EIB (p-value > 0.05). However, the data indicated that there was a relationship between health personnel support and EIB with p-value < 0.05. Conclusion: The result of the study suggested that the variables under investigation showed different impacts. Maternal knowledge and health workers' support were the two variables which were correlated to EIB whereas partner support showed no correlation at all.